Salt Spray Corrosion of 2060-T8 Al–Li Alloy in an Aggressive Environment - Zhengquan Zhang; Yuling Wang; Li Liangfeng (Advances in Materials Science and Engineering)
The phase and microstructure of corrosion product formed on 2060-T8 Al–Li alloy have been investigated effectively by SEM and XRD after salt spray corrosion. It was found that the corrosion product growth rate can be divided into three stages: the main phases of corrosion product were Al2O3, Al(OH)3, and AlOOH phases; as the increasing of salt spray time, the phase angle of A12O3 shifts slightly to the left at 31.8°; and the phase angle of A12O3 first shifts to the left, then to the right at 38.6°. The formation and evolution model of salt spray droplet was built, and the formation mechanism of corrosion product was also analyzed. This alloy shows a sensitive corrosion performance to the salt spray environment.